LUX-Lung 3: redundancy, toxicity or a major step forward? Afatinib as front-line therapy for patients with metastatic EGFR-mutated lung cancer. (March 2014) - Köhler, Jens; Schuler, Martin
ABSTRACT: : Mutant EGF receptor (EGFR) is an attractive therapeutic target in patients with metastatic non-small cell lung cancer (NSCLC). A new paradigm has been defined using ATP-competitive EGFR tyrosine kinase inhibitors (TKIs), gefitinib and erlotinib, as the most effective first-line treatment. However, clinical benefit of EGFR-TKI is only transient and limited by primary or acquired resistance. Afatinib has been developed as a highly potent, irreversible inhibitor of EGFR, HER2 and ErbB4, as well as transphosphorylation of ErbB3. The clinical activity of afatinib in lung cancer has been extensively studied in the LUX-Lung series of trials. LUX-Lung 3 was a pivotal randomized Phase III study that recently led to the approval of afatinib (Gilotrif ® ) in several countries for treatment of patients with metastatic NSCLC harboring somatic EGFR gene mutations. Here, we review the rationale, study design including end points, results and implications of this trial for current and future EGFR genotype-directed lung cancer therapies.